2015
DOI: 10.1111/adb.12239
|View full text |Cite
|
Sign up to set email alerts
|

Increased ventral-striatal activity during monetary decision making is a marker of problem poker gambling severity

Abstract: The aim of this study was to examine the impact of different neural systems on monetary decision-making in frequent poker gamblers, who vary in their degree of problem gambling. Fifteen frequent poker players, ranging from non-problem to high-problem gambling, and fifteen non-gambler controls were scanned using fMRI while performing the Iowa Gambling Task (IGT). During IGT deck selection, between-groups fMRI analyses showed that frequent poker gamblers exhibited higher ventral–striatal but lower dorsolateral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Additionally, Voss et al (2008) used a color discrimination task to demonstrate that results in ambiguous situations were more influenced by the motivational level. Furthermore, both motivation and decision-making under uncertainty seem to be altered in the same neuropsychiatric (Cella et al, 2010;Treadway et al, 2012Treadway et al, , 2014Kim et al, 2016) and addictive disorders (Brevers et al, 2016), lending support for a link between these two concepts. Moreover, in an electrophysiological study using eventrelated potentials (ERPs), a P300 was observed following a loss of money in participants able to develop a correct strategy at the IGT (Giustiniani et al, 2015).…”
Section: Introductionmentioning
confidence: 89%
“…Additionally, Voss et al (2008) used a color discrimination task to demonstrate that results in ambiguous situations were more influenced by the motivational level. Furthermore, both motivation and decision-making under uncertainty seem to be altered in the same neuropsychiatric (Cella et al, 2010;Treadway et al, 2012Treadway et al, , 2014Kim et al, 2016) and addictive disorders (Brevers et al, 2016), lending support for a link between these two concepts. Moreover, in an electrophysiological study using eventrelated potentials (ERPs), a P300 was observed following a loss of money in participants able to develop a correct strategy at the IGT (Giustiniani et al, 2015).…”
Section: Introductionmentioning
confidence: 89%
“…In an fMRI study with healthy adults, Xue, Lu, Levin, and Bechara (2010) suggest that activation in the insula signals a gambling urge (Tényi, Gyimesi, Kovács, Tényi, & Janszky, 2016). Moreover, it has been proposed (Brevers, Noël, He, Melrose, & Bechara, 2016;Verdejo-García & Bechara, 2009) that this urge might facilitate the seeking of immediate rewards.…”
Section: Group Differencesmentioning
confidence: 99%
“…Similarly, the IPL, implicated in processing uncertainty (Vickery and Jiang, 2009), has been found to function differently during decision-making in individuals with and without IGD (Dong and Potenza, 2015). In addition, the insula, OFC and ACC have been implicated in risk representation (Naqvi et al, 2014, Schonberg et al, 2011), the abnormal activation of which has been related to impaired risk-taking in addicted populations (Brevers et al, 2015, Gowin et al, 2014, Paulus et al, 2008). Taken together, these central brain structures may contribute importantly to impaired decision-making in IGD.…”
Section: Introductionmentioning
confidence: 99%